EFEKTIVITAS BEASISWA KIP-K SEBAGAI INVESTASI SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS TENAGA KERJA MASA DEPAN - Ghanis Anggun Pramesty; Tegar Hidayat; Rantika; Jevano Gilang Savio; Nina Farliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human resource development is a strategic factor in increasing workforce competitiveness in the era of globalization. However, economic constraints remain a barrier to access to higher education. Therefore, the government introduced the Indonesia Smart College Card (KIP-K) program to provide financial support for students from low-income families. This study aims to analyze the effectiveness of the KIP-K program as a human resource investment in improving the quality of the future workforce. The method used was a quantitative approach using a survey questionnaire distributed to 30 KIP-K recipient students at the Faculty of Economics and Business, Universitas Negeri Semarang (FEB UNNES), which was analyzed descriptively. The results indicate that the KIP-K program contributes to improving educational access, learning motivation, and the development of student skills and engagement, although inequalities in its utilization remain. This research is expected to serve as an evaluation tool for the government and educational institutions in optimizing the program and as a reference for further research related to human resource development.